2021
DOI: 10.1002/jso.26391
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pathological tumor regression grade in locally advanced gastric cancer: New perspectives from a single‐center experience

Abstract: Background and Objective Perioperative chemotherapy (PC) with radical surgery represents the gold standard of treatment for resectable advanced gastric cancer (GC). The prognostic value of pathological tumor regression grade (TRG) induced by neoadjuvant chemotherapy (NACT) is not clearly established. This study aimed to investigate the correlation between TRG and survival in GC. Methods Patients affected by advanced GC undergoing PC and radical surgery were considered. TRG was assessed for each patient accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 39 publications
3
13
2
Order By: Relevance
“…Furthermore, multivariate analysis by Cox regression showed that the TRG was an independent risk factor affecting the prognosis of patients. This result was consistent with the findings of Lombardi et al (12), whose study included 100 GC patients who received NACT and showed that the TRG could be an independent prognostic factor by exploring the correlation between the TRG and DFS and DSS. Also, a previous meta-analysis involving 17 studies suggested that pathological response was significantly related to the improvement of OS in patients with gastroesophageal junction tumors, and proposed that the TRG should be considered a strong prognostic factor to guide postoperative treatment and followup (20).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, multivariate analysis by Cox regression showed that the TRG was an independent risk factor affecting the prognosis of patients. This result was consistent with the findings of Lombardi et al (12), whose study included 100 GC patients who received NACT and showed that the TRG could be an independent prognostic factor by exploring the correlation between the TRG and DFS and DSS. Also, a previous meta-analysis involving 17 studies suggested that pathological response was significantly related to the improvement of OS in patients with gastroesophageal junction tumors, and proposed that the TRG should be considered a strong prognostic factor to guide postoperative treatment and followup (20).…”
Section: Discussionsupporting
confidence: 92%
“…In the field of GC, Blackham et al analyzed 58 patients with surgical resection of GC after NACT in two medical institutions and found that TRG could not predict prognostic survival of patients (11). However, Lombardi et al investigated the correlation between TRG and diseasefree survival (DFS) and disease-specific survival (DSS) in 100 GC patients treated with NACT, and found that TRG was an independent prognostic factor (12). Hence, there is no unified standard for its application in neoadjuvant therapy for GC, and the prognostic value of GC remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Although complete tumor regression is generally associated with the best patient outcome, there is little consensus regarding prognostic value in partial or subtotal regression. Despite these uncertainties, several studies came to the conclusion, that a TBR < 10% is significantly associated with superior survival, which we also confirmed, now using digital image analysis [18,19,60]. On the contrary, increasing the cut-off value to 20% or dividing into quartiles showed no statistical significance in our cohort.…”
Section: Neoadjuvant Chemotherapy Inhibits Rapidly Proliferating Tumo...supporting
confidence: 81%
“…The same conclusion was reached in further subgroup analysis in the ypStage II/III, LVI positive, and PNI positive groups. Different studies ( 40 , 41 ) have shown that pathological TRG grade was a predictor of OS and RFS in LAGC patients. Patients with good response had obvious tumor tissue fibrosis, less tumor residual, and down-staging, which were correlated with better prognosis.…”
Section: Discussionmentioning
confidence: 99%